Preservation of Intangible Cultural Heritage Using Advance Digital Technology: Issues and Challenges - Idris, Muhammad Zaffwan; Mustaffa, Norsimaa Binti; Yusoff, Syed Osman Syed (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2016)
The emerging concern on intangible heritage in the international arena reflects the fear of cultural homogeneity, diminishing cultural diversity and human creativity. Cultural heritage is a symbol spiritual and intellectual wealth of a civilization, while intangible cultural heritage is associated to tradition and living expressions. There is a need to preserve these fragile assets so they would someday be oblivious in the modern world. Ironically, the potential strategy in preserving the intangible cultural heritage lies in the current advanced digital technology. This paper highlights major issues and challenges in the intangible cultural heritage preservation through technology, with regards to the content and the purpose associated to it.